The effect of the media comic education on science learning outcome - Awdie Fathan Alie; Mohammad Liwa Ilhamdi; Heri Hadi Saputra (Jurnal Pijar Mipa, 2021)
The purpose of this study is to determine the effect of implementing educational comic media on student learning outcomes for science content of fifth-grade students at SDN 2 Pengenjek. This type of research is an experimental research design with a quasi-experimental type of non-equivalent control group design. The data collection technique used is an observation of the learning implementation applying educational comic media and tests to collect data on learning outcomes using multiple-choice tests. The research population was 44 respondents, namely the fifth-grade students of SDN 2 Pengenjek, determined by the saturated sampling technique. The data were analyzed using descriptive statistics and inferential statistical analysis (t-test). The results showed the average value in the experimental class was 69.09 while the class was 44.85. The results of the t-test analysis on studentsÃ¢â¬â¢ science learning outcomes obtained a significance value of 0.000 at a significance level of 5%. Based on these results, it can be concluded that there is an impact of using educational comic media on the learning outcomes of fifth-grade students at SDN 2 Pengenjek.